2016
DOI: 10.1200/jco.2015.61.5427
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes After Choice for Contralateral Prophylactic Mastectomy

Abstract: Choice for CPM was associated with an improvement in breast satisfaction and psychosocial well-being. However, the magnitude of the effect may be too small to be clinically meaningful. Such patient-reported outcomes data are important to consider when counseling women contemplating CPM as part of their breast cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
60
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 27 publications
1
60
2
Order By: Relevance
“…CPM was not associated with worse physical or sexual well-being, and while breast satisfaction and psychosocial well-being were statistically better in women who had CPM vs. mastectomy alone, as noted by the authors, the differences between the two groups were small, and likely not clinically significant (3). Similarly, Koslow et al (in a study that also assessed post-surgical outcomes with the BREAST-Q), found that among women who had implant-based reconstruction, breast satisfaction was higher among those who had CPM compared to women who had mastectomy alone, however psychosocial, physical, and sexual well-being were similar between the two surgical groups (5).…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…CPM was not associated with worse physical or sexual well-being, and while breast satisfaction and psychosocial well-being were statistically better in women who had CPM vs. mastectomy alone, as noted by the authors, the differences between the two groups were small, and likely not clinically significant (3). Similarly, Koslow et al (in a study that also assessed post-surgical outcomes with the BREAST-Q), found that among women who had implant-based reconstruction, breast satisfaction was higher among those who had CPM compared to women who had mastectomy alone, however psychosocial, physical, and sexual well-being were similar between the two surgical groups (5).…”
mentioning
confidence: 49%
“…As such the authors concluded that psychosocial functioning among women who had CPM was similar to those who had mastectomy alone, regardless of the length of time that had passed since their surgery (3). Importantly, psychosocial functioning trended positively over time for all patients, independent of their choice for CPM, which is good news for long-term breast cancer survivors (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it would be helpful to include information about absolute risk 9 for surgical complications and for contralateral breast cancer after CPM, as well as more recent data on quality of life after CPM. [10][11][12] In addition, women should be provided with information about breast reconstruction options 13 and should be encouraged to consult with a reconstructive surgeon 1 to ensure that they are better informed about the potential benefits and risks of reconstructive procedures before making a final decision. Recent studies that collected patient-reported outcomes (PROs) using a wellvalidated, breast surgery-specific instrument (BREAST-Q) 14 demonstrate that breast reconstruction can improve women's satisfaction as well as their psychosocial, physical, and sexual well-being after mastectomy.…”
mentioning
confidence: 99%
“…For example, it would be helpful to include information about absolute risk 9 for surgical complications and for contralateral breast cancer after CPM, as well as more recent data on quality of life after CPM. [10][11][12] In addition, women should be provided with information about breast reconstruction options 13 and …”
mentioning
confidence: 99%